Verification of building settlement by using ground penetrating radar - Munirah Ahmad Syukri, 1996-, author (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2019)
Project Paper (Sarjana Muda Kejuruteraan (Geomatik)) - Universiti Teknologi Malaysia, 2019